(untitled) (Cahiers Africains de rhétorique, 2025)
This contribution explores the points of convergence between The son-of-the-male-woman and Porcupine Memories. The aim is to show that in terms of composition, these two texts are polymorphic spaces where the morphology of the African tale and the codes of the novelistic narrative mingle. Therefore, this study aims to show how the use of the structure of African tales in the narrative enunciation and the programmatic construction of the characters give birth to a tale-novel, better to a transgeneric novel. To do this, the methodological approach convened is inspired by the theory of Cultural Studies of Maxime Cervulle and Nelly Quemener, the transcultural approach of Josias Semujanga (2001). At the end of this study, it appears that the use of cultural bias and canonical forms inherited from the West in the works of Maurice Bandaman and Alain Mabanckou contributes to transcending the boundaries between the endogenous and the exogenous, to forging a world-writing, which advocates the relationship, the interconnection between narrative forms. Fiction writingthus becomes the place where globalization is explicitly deployed.